An intervention study on a hospital-community integrated management model of tobacco dependence based on a community intervention trial - Qiao, Kun; Liu, Han; Li, Xingming; Jin, Qianying; Wang, Yao; Gu, Mingyu; Bai, Xinyuan; Qin, Tingting; Yang, Yutong (Frontiers in Psychiatry, 2023)
Objective: To assess the effect of the hospital-community integrated management model of tobacco dependence on smoking cessation among community residents compared with a brief smoking cessation intervention. Methods: Our study recruited 651 smokers who were willing to quit in 19 communities in Beijing and conducted a 6-month smoking cessation intervention. The control group receiving a brief smoking cessation intervention and the pilot group receiving an integrated smoking cessation intervention. Intention-to-treat analysis (ITT) and generalized estimating equations were used to assess the effects of the integrated intervention and smoking cessation medication on average number of cigarettes smoked per day (ACSD) and smoking cessation rate. Results: Simple effects analysis showed that smokers taking medication had significantly lower ACSD than those not taking medication at follow-up, the control group reduced smoking by 3.270, 4.830 and 4.760 cigarettes in the first, third and sixth months respectively, while the pilot group reduced by 6.230, 5.820 and 4.100 cigarettes (P < 0.05). The integrated intervention significantly reduced ACSD among medication-taking smokers at 1st month (reduced by 3.420，P < 0.05) and 3rd month (reduced by 2.050，P < 0.05), but had no significant effect among non-medication taking smokers. The 3rd month smoking cessation rate among medication-taking smokers was 27.0%, which was significantly higher than the smokers with brief smoking cessation intervention. Conclusion: The integrated hospital-community intervention can significantly promote smoking cessation among smokers taking medication, but the issue of payment for medication and additional labor compensation for medical staff should be addressed before its popularization.